Phase 2 study of cetuximab (Erbitux) in patients with progressive or recurrent endometrial cancer. Issue 11 (November 2020) - Slomovitz, Brian M; Chelariu-Raicu, Anca; Schmeler, Kathleen M; Lu, Karen H; Gershenson, David M; Wolf, Judith; Coleman, Robert L
Abstract : Introduction: Overexpression of the epidermal growth factor receptor (EGFR) found in common subtypes of endometrial cancer has been associated with advanced stage disease and a poor prognosis. The purpose of this phase 2 study was to evaluate the efficacy and safety of cetuximab in patients with recurrent endometrial cancer. Methods: The study was an open-label phase 2 clinical trial conducted at two institutions. Patients with recurrent or progressive endometrial cancer of any histologic type with the exception of uterine sarcoma received cetuximab at an initial dose of 400 mg/m 2 IV followed by weekly doses of 250 mg/m 2 . One cycle was considered 4 weeks of treatment. The primary efficacy endpoint was clinical benefit response, defined as a complete or partial response or prolonged stable disease (>8 weeks) by RECIST 1.0 criteria. Results: A total of 30 patients were enrolled with a median age of 64 years (range 42–83). Of the 20 evaluable patients, three (15%) had clinical benefit response (one complete response, two stable disease). The patient with a clinical benefit response received a total of 27 cycles and the two patients with stable disease were taken off the study due to progression after four and six cycles, respectively. Of the 10 inevaluable patients, nine received ⩽1 cycle due to clinical deterioration and one had an anaphylactic reaction. One patient had a grade 3 rash which resolved after a delay in treatment. No dose reduction was reported. Conclusions: In this cohort, single agent therapy with cetuximab was well tolerated and had a 15% clinical benefit response. Further studies are required to better identify patients who may respond to this treatment.